Overcoming Cisplatin’s Challenges: A Promising Future in Cancer Care; A Comprehensive Review - Abedini Nazari, Najmeh; Omidi Sarajar, Behnam; Azarshin, Seyedeh Zohreh; Javani Jouni, Fatemeh; Razzaghi, Zahra; Zafari, Jaber (International Journal of Medical Toxicology and Forensic Medicine, 2023)
Background: Cisplatin’s common use as an anti-neoplastic drug poses significant challenges due to its adverse effects, including renal disorders, neuropathies, hearing impairment, and gastrointestinal issues. Methods: A comprehensive search was done across major bibliographic databases, including PubMed, Embase, Web of Science, Google Scholar, and Scopus on cisplatin’s application in various cancer treatments. A manual examination of article reference lists was conducted, collecting data from 1990 to October 2023 for up-to-date research analysis. Results: Cisplatin primarily acts by binding to DNA in the cell nucleus and disrupting DNA transcription and replication, leading to cytotoxicity and malignant cell destruction. Mechanisms of resistance included altered drug absorption, increased efflux and detoxification, modified targets, and increased DNA repair. Interactions with matrix proteins, pH changes, and food affect cisplatin effectiveness. Cisplatin-induced DNA damage mainly forms DNA adducts, causing intra- and inter-strand cross-links. Despite its therapeutic benefits, inevitable adverse effects, like nephrotoxicity, ototoxicity, gastrointestinal diseases, hepatotoxicity, cardiovascular issues, and neuropathy exist. Strategies to mitigate these include hydration therapy, thiol-containing agents, antioxidants, and modulators. Combination therapy enhances cisplatin efficacy. Conclusion: Cisplatin is a potent anticancer tool marked by challenges from adverse effects and emerging resistance. Ongoing research focuses on combined therapeutic approaches and supports interventions to enhance efficacy and reduce adverse effects, fostering optimism for better cancer treatments.